2022
DOI: 10.5644/ama2006-124.369
|View full text |Cite
|
Sign up to set email alerts
|

Styloid Process Length Variations: An Osteological Study

Abstract: <p><strong>Objective</strong>. The objective of this study was to study the morphometry of the styloid process of the temporal bone and the prevalence of an elongated styloid process in relation to side and gender.</p><p><strong>Material and Method</strong>. The present study included 200 human skulls which were procured from the rich osteological collections of the Department of Anatomy, Faculty of Medicine, University of Sarajevo. The styloid process was observed mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…In cases where the elongated styloid process was present unilaterally, when compared to which side was most affected (right or left), we observed a statistically significant difference, where changes on the right side (65.2%) were more prevalent than on the left side (34.8%), which is consistent with another study conducted through the retrospective analysis of medical records of patients with Eagle Syndrome, underwent excision of the styloid process, where it was observed that 65% of the patients had the right side affected, while 35% had the styloid process elongated on the left side (GOVINDARAJALU; SHARMA; PARSANA, 2020). However, some authors report having observed a higher prevalence on the left side than on the right side (KAPUR et al, 2022;GUIMARÃES et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In cases where the elongated styloid process was present unilaterally, when compared to which side was most affected (right or left), we observed a statistically significant difference, where changes on the right side (65.2%) were more prevalent than on the left side (34.8%), which is consistent with another study conducted through the retrospective analysis of medical records of patients with Eagle Syndrome, underwent excision of the styloid process, where it was observed that 65% of the patients had the right side affected, while 35% had the styloid process elongated on the left side (GOVINDARAJALU; SHARMA; PARSANA, 2020). However, some authors report having observed a higher prevalence on the left side than on the right side (KAPUR et al, 2022;GUIMARÃES et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In a systematic review study, the authors stated that the highest mean about the length of the styloid process was observed in a group whose individuals were aged > 54 years, that is, apparently there is an association between the length of this structure and the increase in age, which suggests that the length of this structure can be considered a continuous variable, considering that this tends to increase with the age of the individual (BRUNO et al, 2022;BRUNO et al, 2017). However, Kapur et al (2022) stated that the length of the styloid process may present variations due to differences related to different populations and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Its length varies from 5 mm to 50 mm, with the average normal length being between 20 and 30 mm. 7 8 The stylohyoid ligament connects the styloid process to the lesser horn of the hyoid bone, albeit at a distance. Together, these structures comprise what is known as the stylohyoid chain, also referred to as the stylohyoid complex or apparatus.…”
mentioning
confidence: 99%
“…9 The stylohyoid chain can undergo a discrete osteogenic transformation, which involves the elongation of the styloid process and/or the ossification of the stylohyoid ligament. 8 9…”
mentioning
confidence: 99%
“…Neste estudo, os valores foram maiores do que os de Nunes et al (2021) e Souza et al (2020). Em mais um estudo osteométrico, agora em processos estiloides normais, até 30mm,Kapur et al (2022) utilizando 200 crânios da Universidade de Sarajevo, em 7% dos casos encontraram alongamento, próximo ao resultadode Cavalcante et al (2018). De acordo com este estudo, a média dos processos estiloides normais foram 24,05mm para o sexo feminino e 25,95mm para o sexo masculino.…”
unclassified